PERSEPSI KARYAWAN TENTANG PENERAPAN SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA (SMK3) - Lumowa, Fresy (Lasalle Health Journal, 2023)
Introduction: The Occupational Safety and Health (OSH) management system is very important to be implemented in all workplaces, especially workplaces that have a high risk of accidents and high potential for Occupational Diseases. Law No. 1 of 1970 concerning Occupational Safety whereby every workplace is required to implement an Occupational Safety and Health Management System (OSHMS) in order to obtain safety guarantees and avoid illness while working. Objective: To find out employees' perceptions of the implementation of SMK3. Method: Using qualitative methods with in-depth interview techniques to 7 informants. Results: Employees of PT Mitra Jaya Samudera have sufficient perception of the OSH management system, where several informants gave almost the same statement about OSH but have not been able to independently implement the work risk control hierarchy because the company has not implemented the OSH Management System on Standard Operating Procedures (SOP), so employees are not skilled at implementing OSHMS. The work process is carried out based on directions from field supervisors, not General OSH experts in accordance with applicable regulations, so work accidents in companies often occur. Conclusion: Employees have knowledge of OSH but have not properly carried out OSH procedures, because the company has not implemented company OSHMS and has not been supervised by general OSH experts. Companies need to apply OSHMS so that all employees can carry out OSH properly, and avoid work-related accidents and diseases